Beneficiation of selected pesticides and an antihyperlipidemic agent via cyclodextrin complexation and co-crystallization - Maurel, Vaughan Jean (Department of Chemistry, 2017)
The applications of many bioactive molecules are limited by their undesirable physicochemical properties, such as poor aqueous solubility and low thermal stability. The agrochemicals methyl- 2,5-dichlorobenzoate (fungicide, DCB) and fenthion (insecticide), as well as the medicinal compound acipimox (lipid-lowering agent) were selected for study in this context. The cyclodextrin (CD) complexes γ-CD/DCB, 2,6-dimethylated-β-CD/DCB, β-CD/fenthion, permethylated α-CD/fenthion and permethylated β-CD/fenthion, were synthesised. 1H-NMR spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and hot stage microscopy (HSM) were used to assess their stoichiometries and thermal behaviours. The complexes 2,6-dimethylated-β-CD/DCB, permethylated α-CD/fenthion and permethylated β-CD/fenthion have 1:1 host-guest stoichiometries, while those for γ-CD/DCB and β-CD/fenthion are 3:4 and 2:1 respectively. Single crystal X-ray structures were elucidated to investigate the modes of DCB inclusion and crystal packing. All of the solid complexes displayed higher thermal stabilities than those of the untreated pesticides. Furthermore, the volatility of the insecticide fenthion (a liquid at 25 ᵒC) was significantly reduced by its transformation to a solid on CDcomplex formation. The solution-state behaviour of fenthion was qualitatively evaluated using UV-visible spectrophotometry and induced circular dichroism. Phase solubility profiles at 25 ᵒC were of type Bs for solubilisation of DCB by β-CD and (2-hydroxypropyl)-β-CD, and for solubilisation of fenthion by β-CD, the respective 1:1 association constants being 737 ± 108 M⁻¹, 412 ± 53 M⁻¹ and 789 ± 170 M⁻¹. For solubilisation of fenthion by (2-hydroxypropyl)-β-CD and randomlymethylated β-CD, AN- and AP-type behaviours were recorded respectively, with association constants 1863 ± 26 M⁻¹ and 3582 ± 106 M⁻¹ respectively. Eight multi-component crystalline systems (co-crystals and salts) of acipimox were isolated via its reaction with co-formers 4-aminobenzamide, 4-aminopyridine, benzamide, isonicotinamide, tranexamic acid and urea. NMR spectroscopy revealed 1:1 stoichiometries for all products. Their designation as salts or co-crystals was based on unequivocal evidence gleaned from single crystal X-ray structural studies, these assignments being confirmed by infrared spectroscopy. The melting points and decomposition temperatures of the products containing the coformers 4- aminobenzamide, 4-aminopyridine, isonicotinamide and tranexamic acid were significantly higher than those of untreated acipimox. Equilibrium aqueous solubilities of the multicomponent systems ranged from 0.31 to 2.77 times those of untreated acipimox.